From feed to field: effect of dietary protein level and use of a blend of feed additives on gaseous emissions from growing-finishing pig slurry - Fuertes, Esperanza; Sarri, Laura; Carnicero, Rodrigo; Pérez-Calvo, Estefania; Calderón, Álvaro; Balcells, Joaquim; Seradj, Ahmad Reza; Cantero-Martínez, Carlos; Fernández-Ortega, Jesús; de la Fuente, Gabriel (Frontiers in Animal Science, 2025)
The environmental impact of livestock waste has driven the need for nutritional strategies to enhance digestive efficiency in pigs, aiming to reduce nutrient excretion and associated emissions of pollutants like ammonia (NH3) and greenhouse gases (GHG). This study investigated the effects of dietary crude protein (CP) reduction by 1.5%, combined with supplementation of a dietary treatment that included feed additives and higher soluble fiber levels, on nutrient digestibility, slurry composition, and emissions across growing and finishing phases. Eighty male pigs were assigned to four different diets in a 13-week trial under a 2 × 2 factorial design: standard protein (SP) and low protein (LP) diets, with or without the dietary treatment. Key measurements included slurry composition, NH3-N and CH4 emissions, and crop yield when slurry was applied as fertilizer. The low-protein diet supplemented with additives (LPA) significantly reduced slurry pH (P ≤ 0.001) and urinary NH3-N excretion (interaction, P = 0.03), improving nutrient digestibility and lowering organic matter content in slurry (P < 0.05). NH3 emissions from the room and slurry pit decreased by over 38%, while CH4 emissions, although higher in LP diets, were mitigated with the LPA diet. Field application of slurry as fertilizer resulted in trends favoring sustainable wheat production, with increased yield and nitrogen use efficiency, alongside reduced CH4 emissions (P < 0.001). These findings underscore the potential of combined dietary strategies to mitigate environmental impacts while enhancing agricultural sustainability.